Shared deliberate practice: a case study of elite handball team training - Lund, O.; Musaeus, P.; Krogh Christensen, M. (Athletic Insight Journal, 2013)
In this case study of a Danish elite handball team, we explore team learning processes in order to examine to what extent team members` development of expertise is a shared deliberate practice. By drawing from theoretical frameworks on expertise and deliberate practice (Ericsson, 2006) and team cognition (Salas, Fiore, and Letsky, 2012), we aim to answer what characterizes efficient and successful handball team training.The case study involved participant observation and interviews, and it included the female first team in a Danish handball club Randers HK. The team is amongst the best three teams in Denmark. In particular, the case studyfound that important factors for shared deliberate practice are concentration, feedback and role modeling. There are four theoretical findings. 1. Deliberate practice in team sport is a shared activity. 2. Both structured tactical training and match training are deliberate practices. 3. Concentration mediates team cognitive skills. 4. Feedback and role modeling mediate team cognitive skills. From an applied perspective, this study points to the value of seeing team sport as necessitating shared deliberate practice. Team players need to train shared understanding and learn how to negotiate the coach`s orchestration of the game plan. Specifically, the results may lead experienced coaches in high performance team sports to use experienced athletes to engage in verbal feedback and being explicit role models to less experienced players.